If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + x = 2(5 + x) 15 + x = (5 * 2 + x * 2) 15 + x = (10 + 2x) Solving 15 + x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + x + -2x = 10 + 2x + -2x Combine like terms: x + -2x = -1x 15 + -1x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + -1x = 10 + 0 15 + -1x = 10 Add '-15' to each side of the equation. 15 + -15 + -1x = 10 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 10 + -15 -1x = 10 + -15 Combine like terms: 10 + -15 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 15x=10x | | 12=-6(y-4) | | 30x=5x | | 3x+5x-30=180 | | 128-6x=12x+24 | | 2x=14/3(4+2x) | | -106-7x=7x+20 | | 1/7(x+8)=3 | | 6=-5x+2x | | 3x-24=2x+1 | | 26x+11x-1=0 | | 3x^3-21x^2=54x | | 4x^3-y=8 | | 7=(-3)-2w | | 3(x+1)-2(3x+7)=14 | | -8.5x-5y+12-3.5x-16= | | x^4+12x^3-8x^2=0 | | -8.5x-5y+12-3.5x= | | x^4+12x^3-45x^2=0 | | 3m+7.5= | | 0=-4t^2+24t | | x^4+7x^3-30x^2=0 | | x^2-10x+23=0 | | 19=(-2x)+4 | | 9-3p=8 | | 2x^2+50x+9=5 | | 4x^2-15x-97=0 | | 0.5x+19.3=x-5.55 | | 2x^2+693=4x | | 0.9x+2.64=-0.5x+0.64 | | x^3+5x^2-10x=0 | | 600x-0.32=400x+0.94 |